Learning Development - Penland, Patrick R. (Journal of Information and Knowledge, 1977)
Describes the basic role of verbal behavior in a learning process in the context of non-verbal cues. Discusses the learning development in three aspects, consultant as a Behavior Developer, Human Development as a Behavioural System, and Methods of Helping consultant. Professional guidance is prescribed to be the engendering of the tactics within clients as processes which will facilitate change in the affective, cognitive, and motor domains. The verbal counter parts of these tactics, are framed into the form of questions. Which together with supportive non-verbals elicit analogous behavior by the client.